The Influence of Elementary School Principal's Transformational Leadership Behavior in Cultivating Entrepreneurial Character of the Millennial Generation - Riswandi Riswandi; Aradatullah Dita Illahiyah; Deviyanti Pangestu; Nur Ridha Utami (Universitas Muhammadiyah Enrekang, 2023)
The rapid and complex changes in education today demand the presence of leaders who are able to overcome the challenges. Principals who practice transformational leadership encourage millennial teachers to have a clear vision, flexibility and the ability to cope with changes in education. The purpose of this study was to analyze and determine the effect of transformational leadership behavior of elementary school principals on building the entrepreneurship character of the millennial generation in Tanjung Karang Barat Sub-district, Bandar Lampung City. This research uses a quantitative approach. The population in this study was 131 elementary school educators in Tanjung Karang Barat District, Bandar Lampung City so that 56 educators. Data collection was carried out using a questionnaire. Data analysis used simple regression which had previously been carried out regression prerequisite tests, namely normality test and linearity test. The results of this study indicate that there is a positive and significant effect of transformational leadership behavior of elementary school principals on the entrepreneurial character of the millennial generation in Tanjung Karang Barat District, Bandar Lampung City with the acquisition of the namely 5.276> 2.005. The conclusion in this study is that with inspirational and empowering leadership, principals can motivate and influence millennial educators to build an attitude of entrepreneurship, innovation and independence needed to face real-world challenges and contribute positively to the world of education and society at large.